A Group-Based Community Reinforcement Approach of Cognitive Behavioral Therapy Program to Improve Self-Care Behavior of Patients With Type 2 Diabetes - Pan, Xiaoqun; Wang, Hongyu; Hong, Xin; Zheng, Chunzao; Wan, Yanan; Buys, Nicholas; Zhang, Yongqing; Sun, Jing (Frontiers in Psychiatry, 2020)
Introduction: This study evaluated a cognitive behavioural based self-care intervention program on diabetes management in individuals with type 2 diabetes in Jiangsu Province, China. People with type 2 diabetes were recruited to a 6 month, prospective, intervention study. Methods：The intervention group (n=296) received an intensive cognitive behavioural based self-care intervention, including group activities, frequent blood glucose monitoring, nutritional counselling, diabetes-specific meal and a weekly progress report. The control group (n=110) received diabetes education, including diet and physical activity instruction only. Assessment data was obtained at baseline, and after 12 and/or 24 weeks of intervention. The intention to treat method was used to assess the effectiveness of the intervention program. Results The intervention group showed improved fasting blood glucose, HbA1c, systolic and diastolic blood pressures compared to the control group. The intervention group also had significantly improved knowledge and self-care behaviour, and general health. Conclusion: This study demonstrates that significant improvement in glycaemic control and markers of cardiovascular health can occur in Chinese people with type 2 diabetes following a CBT based intervention program that includes diabetes education, frequent blood glucose monitoring and daily use of a diabetes-specific meal plan, suggesting CBT is beneficial to improve health outcome in patients with type 2 diabetes.